Micro-Current Stimulation Has Potential Effects of Hair Growth-Promotion on Human Hair Follicle-Derived Papilla Cells and Animal Model - Donghyun Hwang (International Journal of Molecular Sciences, 2021)
Recently, a variety of safe and effective non-pharmacological methods have been introduced as new treatments of alopecia. Micro-current electrical stimulation (MCS) is one of them. It is generally known to facilitate cell proliferation and differentiation and promote cell migration and ATP synthesis. This study aimed to investigate the hair growth-promoting effect of MCS on human hair follicle-derived papilla cells (HFDPC) and a telogenic mice model. We examined changes in cell proliferation, migration, and cell cycle progression with MCS-applied HFDPC. The changes of expression of the cell cycle regulatory proteins, molecules related to the PI3K/AKT/mTOR/Fox01 pathway and Wnt/β-catenin pathway were also examined by immunoblotting. Subsequently, we evaluated the various growth factors in developing hair follicles by RT-PCR in MCS-applied (MCS) mice model. From the results, the MCS-applied groups with specific levels showed effects on HFDPC proliferation and migration and promoted cell cycle progression and the expression of cell cycle-related proteins. Moreover, these levels significantly activated the Wnt/β-catenin pathway and PI3K/AKT/mTOR/Fox01 pathway. Various growth factors in developing hair follicles, including Wnts, FGFs, IGF-1, and VEGF-B except for VEGF-A, significantly increased in MCS-applied mice. Our results may confirm that MCS has hair growth-promoting effect on HFDPC as well as telogenic mice model, suggesting a potential treatment strategy for alopecia.